Fresh Water Snails of Public Health Importance in Canals in Okigwe Imo State Nigeria: Their Infectivity and Implications for Control - Ugochukwu Obisike Victor; Chozuruoke Dike Maduabuchi; Ezinna E Enwereji (International Journal of Health Statistics, 2022)
Studies have linked freshwater snails with human flukes as a result of repeated contacts with contaminated water. This study is aimed to determine the distribution of freshwater snails and their infectivity rates along human dwellings in Okigwe Imo state using Physico-Chemical parameters. Freshwater snails were collected by using long plastic spoons and with hand-picking method. The Physico-Chemical parameters were determined with appropriate instrument and freshwater snails harvested from the site were morphologically identified. One thousand four hundred and nine (1409) freshwater snails belonging to the species Lymneae and Bulinus were collected once a week throughout the period of study with the relative percentage of 43.9%; 29.9% ;26.2% respectively. The infectivity rate was highest in snails that were collected in the month of May compared to those collected in June and July, the rate was 69.2%, 50.1% and 33.6% in the months of May, June and July respectively. Dissolved oxygen (DO), Biological oxygen demand (BOD) and PH were found to significantly influence snail distribution in the site (p<0.05). The finding showed that 54.2% of all the snails collected were infected. The snail distribution observed may give an insight into some aspects of the epidemiology of trematodes infection in Okigwe the site for the study and their potential risks to infect human beings and animals.
Keywords: Intermediate host